Rights of Accused and Victim against Media Victimization: a Critical Examination - Khubalkar, Dr. Deepti; Sharma, Shilpa; Singh Dari, Sukhvinder (Medicine, Law & Society, 2022)
With the advent of technology and communication media, it is now possible to gather and integrate data via a digital medium. Data sharing without authorization via electronic media is referred to as a breach of digital privacy. The right to privacy is a human right that is guaranteed by law in nearly every country and has been extended to those who are under trial/ accused. At the same time, the press, including digital media, has the right to freedom of expression. This paper examines the unwarranted intervention of digital media in the personal lives of both the victim and the accused. Inquisitorial as well as adversarial models of judicial process presume the accused innocent until guilt is proven after following the due process of law. This paper investigate the unrestrained and irresponsible publication of news and posts that violate a person's data privacy and available remedies in the law when rights to privacy are breached. It also comparatively examine privacy laws and legal remedies in the United States, the United Kingdom, and India, and make appropriate recommendations. Study of this paper reveals that in the wake of rising interferences by media, there is no specific statute providing protections.